2022
DOI: 10.3390/plants11030251
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and Stability of Faba Bean (Vicia faba L.) Accessions under Diverse Environments and Herbicide Treatments

Abstract: The adaptability and stability of 37 faba bean (Vicia faba L.) accessions with different levels of tolerance to metribuzin or imazethapyr was assessed across 12 season–location–herbicide experiments. Significant Genotype x environment (GE) interaction was found for the days to flowering (DFLR), plant height (PLHT) and grain yield (GY). Performance and stability of the accessions regarding PLHT and GY were assessed using four different stability parameters: cultivar superiority, static stability, Wricke’s eco-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 68 publications
6
13
0
Order By: Relevance
“…Lower heritability estimates for BY and SY indicated that these traits were highly influenced by environmental factors and controlled a large number of genes with a small effect when compared to phenological traits. These findings are consistent with previous research on fava beans [ 22 ], chickpeas [ 32 ], and lentils [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Lower heritability estimates for BY and SY indicated that these traits were highly influenced by environmental factors and controlled a large number of genes with a small effect when compared to phenological traits. These findings are consistent with previous research on fava beans [ 22 ], chickpeas [ 32 ], and lentils [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous research on lentils and other crops compared stability parameters to advise the breeders on the best method to use for selection. Our findings revealed inconsistencies in genotype ranking, as previously reported in fava beans [ 22 ], lentils [ 33 , 34 ], chickpeas [ 35 ], and sorghum [ 36 ]. Nevertheless, the analysis of Spearman’s coefficient revealed that there were some correlations between these stability parameters.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations